PENGEMBANGAN LKPD BERBASIS CLASSPOINT PADA MATA PELAJARAN IPAS MATERI KERAGAMAN BUDAYA KELAS 4 SEKOLAH DASAR - Citra Oktavia; Wahid Ibnu Zaman; Muhammad Basori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the results of observations, that the lack of teacher motivation in utilizing technology to develop LKPD independently, resulting in a boring learning process and lack of student interest in learning. So the researcher developed LKPD based on classpoint material on cultural diversity. The objectives of this development research are: To determine the validity of LKPD based on classpoint material on cultural diversity in class IV SDN Gayam 1, To determine the practicality of LKPD based on classpoint material on cultural diversity in class IV SDN Gayam 1, To determine the effectiveness of LKPD based on classpoint material on cultural diversity in IV SDN Gayam 1. This study uses a type of research and development (research and development) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) developed by Sugiyono. The results of this study (1) The results of media expert validation 84%, material expert validation 90% and learning device validation 96% with an average validity score of 90%. (2) The results of the teacher's response were 93%, the limited test student response was 100%, the broad test student response was 96% with an average practicality of 96%. (2) The results of the effectiveness of the limited trial with an average value of 92 with a percentage result of 100%, and the broad trial obtained an average value of 87 with a percentage of 92% can be stated as very effective for use in learning activities. Thus, the LKPD based on classpoint material on cultural diversity that was developed can attract students' interest in learning and improve students' learning outcomes.